(untitled) (TAMADDUN NURI JURNALI, 2024)
This scientific article describes the sources related to the history of Khorezm during the Islamic period. Khorezm, known for its rich cultural and scientific heritage, has been studied by many scholars and historians. The article analyzes the works of notable figures such as Ibn Khordadbeh, Al-Biruni, and Mahmud ibn Abbos al-Khorezmi, highlighting the historical significance and geographical position of Khorezm. Additionally, it provides information on the development of education and science in Khorezm, as well as the social and economic life of its cities. This research aims to contribute to a deeper understanding of Khorezm’s role during the Islamic period and its cultural legacy.